Peta Strategi Pengembangan Tvri Stasiun Diy Berbasis Balanced Scorecard - Pancawati, Meidiana; Tjahjono, Heru Kurnianto; Puji RDA, Meika Kurnia (208-7721)
Research undertaken in this thesis is to answer: how management system and strategy applied by TVRI up to now perform. On the basis of this research this study develops an appropriate strategy map on the basis of Balanced Scorecard (BSC) model. Selection of Balanced Scorecard model as an analytical tool is believed that the BSC model contains a comprehensive and coherent management concept. It is comprehensive because it keeps a balance between finanacial perspective / financial performance and non-financial perspective (such as customer perspective, internal business perspective, learning and growth perspective). It is coherent because a performance in one perspective or in other perspectives will influence each others. With clear measuring base for those programs and targets achieved of each perspective, it has made Balanced Scorecard become an accurate measure of performance. In its development, balanced Scorecard has also become an easy working model for the management to communicate strategy and implementing vision and mission into stratetegic and measureable programs. From the research findings, it has been known that each perspective of TVRIâs performance is very weak. In such a manner the strategy is sporadically applied, as just to overcome the existing problem. Less integrated and has no long-term dimension.Therefore, it is needed to have a comprehensive strategy map who easy to be implemented. The strategy map is made based on capacity and in accordance with the organizationâs internal and external environment. It is therefore sound to assume that developing a strategy based upon balanced scorecard is very relevant.